1988
DOI: 10.2307/1941638
|View full text |Cite
|
Sign up to set email alerts
|

Annual Experimental Evaluation of the Effect of Invasion History on Community Structure

Abstract: Fifty—four communities were developed from repeated introductions of 28 phytoplankton species in three different orders of invasion at three different rates. Variation in species richness values in these communities was assignable to invasion order, invasion rate, and the timing between interspecific invasions. Invasion rate was most influential, explaining 21.8—78.8% of the variation on any give date; invasion order never explained >4.3%, and timing explained between 19.7 and 74.9%. All three facets of invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 34 publications
0
86
0
Order By: Relevance
“…Robinson & Dickerson 1987;Robinson & Edgemon 1988). We speculate that introduction frequency will be crucial to persistence of populations with low average individual fitness resulting from inter-specific interactions, particularly in competitively structured communities that, if unperturbed, eventually result in exclusion.…”
Section: Results (A) Hypothesis 1: Realized Population Growth Ratementioning
confidence: 96%
“…Robinson & Dickerson 1987;Robinson & Edgemon 1988). We speculate that introduction frequency will be crucial to persistence of populations with low average individual fitness resulting from inter-specific interactions, particularly in competitively structured communities that, if unperturbed, eventually result in exclusion.…”
Section: Results (A) Hypothesis 1: Realized Population Growth Ratementioning
confidence: 96%
“…Our findings highlighted the importance of density-dependent processes in modulating the effects due to the changes in number and identity of HFSs. Because density-dependent processes are pervasive in nature (Barkai & McQuaid 1988, Robinson & Edgemon 1988, Drake 1991, Rand 2003, Griffin et al 2008, it is desirable that future biodiversity experi-ments explicitly consider density effects with the appropriate designs (He et al 2005, Benedetti-Cecchi 2004, O'Connor & Crowe 2005 to foster progress in understanding of biodiversity-ecosystem functioning relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have suggested that even under similar environmental conditions, very different communities can develop as a result of variation in the timing and sequence of species invasions (but see, for methodological issues, Connell and Sousa 1983;Sousa and Connell 1985;Grover and Lawton 1994). These studies also range from controlled laboratory experiments (e.g., Gilpin et al 1986;Robinson and Dickerson 1987;Robinson and Edgemon 1988;Drake 1991;Drake et al 1993;Lawler 1993), field experiments (Quinn and Robinson 1987;Jenkins and Buikema 1998;Chase 2003a) and observations of natural systems (Cole 1983;McCune and Allen 1985;Petraitis and Latham 1999). Thus, the general conclusion from reading the literature seems to be that in some cases, communities converge to a single equilibrium, regardless of invasion order, whereas in other cases, communities achieve multiple stable equilibria.…”
Section: Empirical Evidence Of Community Assemblymentioning
confidence: 99%